2001
DOI: 10.1136/jnnp.71.3.383
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of the Spiegelberg parenchymal transducer and ventricular fluid pressure

Abstract: The Spiegelberg brain pressure catheter is a low cost implantable intracranial pressure measuring system which has the unique ability to perform regular automatic zeroing. A new version of the catheter has become available with a subdural bolt fixation to allow insertion of the device into the brain parenchyma. The accuracy of this system has been evaluated in comparison with a ventricular fluid pressure method in a series of patients to determine its accuracy and utility in the clinical environment.Hourly rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 6 publications
0
19
0
3
Order By: Relevance
“…12 This problem has been addressed in the balloon-like Spiegelberg transducer which may zero itself every set time interval, although its limited bandwidth may make most of the methods used for the ICP waveform analysis impossible. 13 Contemporary epidural sensors are much more reliable than 10 years ago. But the question as to whether epidural pressure can express ICP with confidence and under all circumstances is still unanswered.…”
Section: Methods Of Measurementmentioning
confidence: 99%
“…12 This problem has been addressed in the balloon-like Spiegelberg transducer which may zero itself every set time interval, although its limited bandwidth may make most of the methods used for the ICP waveform analysis impossible. 13 Contemporary epidural sensors are much more reliable than 10 years ago. But the question as to whether epidural pressure can express ICP with confidence and under all circumstances is still unanswered.…”
Section: Methods Of Measurementmentioning
confidence: 99%
“…8 A CPP of more than 70 mm Hg was maintained using one or more inotropic supports with a central venous pressure between 5 and 10 mg. 8 A CPP of more than 70 mm Hg was maintained using one or more inotropic supports with a central venous pressure between 5 and 10 mg.…”
Section: Multimodality Monitoring: Group Amentioning
confidence: 99%
“…Review of literature reveals a comparison study of the Spiegelberg parenchymal transducer and ventricular fluid pressure. Utilizing an air bladder technology for parenchymal ICP monitoring, this study showed good agreement between the readings from the Spiegelberg transducer with those from the ventricular drain (Chambers et al 2001). …”
Section: Introductionmentioning
confidence: 56%